Moral Disengagements on Iconography of Superhero Films: Black Adam, Captain America: The First Avenger, and Man of Steel - Pasopati, Rommel Utungga; Ramadhani, Riska Dewi; Lutvia, Frefies Lavigni Putri; Andharu, Devito; Fadillah, Muhammad Reza Ishadi (Fakultas Ilmu Budaya, Universitas Mulawarman, 2024)
This paper exposes collateral damage as representation of moral disengagement in the three superhero films of Black Adam, Captain America: The First Avenger, and Man of Steel. Iconography in superhero film represents ambivalent moral justifications. The superheroes must do everything to ‘save’ the world though it is done by embracing evil, destroying surroundings, or using cunning strategies. Any collateral damage in moral disengagement is considered necessary in order to destroy the source of the problem. The superheroes must do everything to save the day though he/she has to kill, to abuse his/her power, and even be ignorant only to focus on bigger things by sacrificing petty things. As the analysis, the moral disengagement is shown through recurring iconography of superheroes who kill other people and destroy the surrounding. The three superhero films indicate that the actions of the superheroes are only focusing on their own moral values. Collateral damage is considered not only as side effect of superheroes’ action, but also as reflection of their moral disengagement. In conclusion, the values that superheroes hold is universal, but actually, those destroy particular matters. Their moral doings are not totally true, but those are justified as one.